Meningkatkan Keterampilan Membaca dan Computational Thinking Siswa Melalui Media Pembelajaran Berbasis Visual Kontekstual - Agung Nasrulloh Saputro; Swasti Maharani; Addy Septyawan; Hendrisa Rizqie Romandoni; Widia Yunita (Journal on Education, 2024)
This research aims to improve students' reading and computational thinking skills through the use of contextual visual-based learning media. Contextual visuals can help students understand the meaning of texts, increase their interest in reading, and increase their motivation to read. This study uses a literature review method with a qualitative approach. The data sources in this study are literature relevant to the research theme, such as scientific journals, books, scientific articles, trusted websites, and research reports. The data collection technique in this study is a documentation study, namely by collecting and analyzing various relevant literature. The data analysis technique in this study is content analysis, namely by identifying, categorizing, and interpreting the content of various literature that has been collected. The results of the study show that the use of contextual visual-based learning media is effective in improving students' reading and computational thinking skills. First, this study shows that contextual visuals can be an effective tool to improve students' reading and computational thinking skills. Second, this study guides teachers in using contextual visuals in reading learning. Third, this study encourages further research on the use of contextual visual-based learning media in other subjects.